Integrated surface-subsurface reservoir zonation of the early Bartonian nummulitic limestone in central Tunisia and eastern Tunisian offshore - Haj Messaoud, Jihede; Thibault, Nicolas; Bomou, Brahimsamba; Adatte, Thierry; Aljahdali, Mohammed H.; Yaich, Chokri (Frontiers in Earth Science, 2024)
The Early Bartonian Reneiche/Siouf member is one of the primary conventional carbonate oil/gas reservoirs to be assessed in Tunisia that demands detailed evaluation. Accurate zonation and modeling of this reservoir require an integrated approach combining surface and subsurface studies. This research focuses on the depositional, diagenetic, and stratigraphic factors affecting reservoir quality and porosity within the Reneiche/Siouf member, utilizing an integrated surface-subsurface analysis. The primary aim is to understand the reservoir zonation of the Reineche Member near Kerkennah archipelago (eastern Tunisian offshore) and its lateral equivalents in central Tunisia the Siouf Member (outcrop analogue). Gamma-ray and sonic logs from the Reineche Member in the southern and southeastern Pelagian Platform (Tunisian offshore) identify three distinct limestone units (A, C, and E). These units transition into a single mud-dominated limestone unit (C) to the east and northeast of the Kerkennah archipelago. In contrast, the western Pelagian Platform (onshore) and Central Tunisia present a different stratigraphy for the Reineche/Siouf Member, comprising two limestone units: the Lower Reneiche Limestone (LRL) and the Upper Reneiche Limestone (URL), corresponding to Units C and E, respectively, separated by the Upper Reneiche Shale (URS) unit. Reservoir porosity and permeability analyses of the outcrop analogs reveal hybrid pore types (depositional and diagenetic), including intragranular, biomouldic, and vuggy pores, resulting from significant dissolution of large bioclasts. In the northern Gulf of Gabes, the Nummulite barrier of the Reineche Member (SW of the Kerkennah archipelago) demonstrates substantial reservoir quality improvement, with porosity reaching up to 30% in Unit C, attributed to intense dissolution, dolomitization (intercrystalline porosity), and fracturing. Diagenetic processes observed in the Siouf Member (Central Tunisia) differ from those in the Reineche Limestone Member (Pelagian Platform). In the Reineche Member, CO2-rich fluids entering through faults and fissures during deep burial diagenesis drive dissolution and dolomitization. Conversely, in the Siouf Member, these processes occur due to short subaerial exposures during meteoric to shallow-burial diagenesis. A key outcome of our study is the comparison between Central Tunisia and the eastern Tunisian offshore, highlighting local tectonic control on reservoir thickness and identifying three upward-thickening sequences in the Siouf Member outcrop. This research is crucial for understanding the Gulf of Gabes and Libyan offshore nummulitic Eocene reservoirs, emphasizing the role of tectonics and sea level changes in shaping reservoir characteristics.